Determinants of Catastrophic Health Expenditure of Households in Indonesia - Afrizal, Rafa Fayza; Hasya, Novira; Harda, Faticha Putri; Alfathin, Wildan Avif; Latifah, Vanissa Nur; Nainggolan, Maxent Rael; Jaelani, Fadillah Rahmah; Sihaloho, Estro Dariatno (Jurnal Ekonomi Kesehatan Indonesia, 2025)
The need for healthcare services due to illness is unpredictable, thus burdening patients economically and posing a risk of catastrophic events. The percentage of households with catastrophic health expenditures is defined as out-of-pocket payments exceeding 10% of the household’s capacity to pay for healthcare. Increasing catastrophic expenditure costs can further deteriorate the household’s financial condition. This study analyzes the determinants of catastrophic health expenditures in Indonesian households. A total of 12,892 household samples from the cross-sectional Indonesian Family Life Survey (IFLS) wave 5 (2014) were used in this study. Using a logistic regression model, this study aims to identify various socioeconomic factors and household members’ health histories that may influence the probability of a household experiencing catastrophic health expenditures. The study results show that socioeconomic factors, including household expenditures (p<0.01), the number of working household members (p<0.01), the number of insured household members (p<0.01), residential area (p<0.1), and the education level of the household head (p<0.01), have a significant influence on catastrophic expenditures. Catastrophic health expenditures are also significantly affected by the health history of household members, including chronic diseases (p<0.01), hospitalization history (p<0.01), and outpatient care (p<0.01). To reduce financial risks, policymakers can design a fair healthcare financing mechanism that addresses socioeconomic vulnerabilities and health risks. Expanding insurance coverage and strengthening financial protection for at-risk households can help alleviate the burden of catastrophic health expenditures.